2017
DOI: 10.25181/jppt.v14i2.147
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisasi, Kesesuaian Lahan dan Teknologi Kelapa Sawit Rakyat di Rawa Pasang Surut Kalimantan Tengah

Abstract: Oil palm extensification in tide land. It's a marginal land which sensitive to degradation. Otherwise, peat is low bearing capacity, subsidence, drying irreversible and close fire and then emission of green house gas. So other soil in the tide land is acid sulfate soils have a pyrite, while be can oxidation can produce of increased soil acidity and ferro and aluminum. Location of research include ine Ex Rice Mega Project ie. Kapuas Regency and Pulang Pisau Regency, and other is East Kotawaringin Regency. Limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
0
9
0
5
Order By: Relevance
“…merupakan tanaman C3 penghasil minyak nabati yang paling efisien (Lamade et al, 2009; Jaafar dan Ibrahim, 2012) dan mampu tumbuh pada berbagai agroekosistem (Firmansyah, 2014). Kelapa sawit mampu menghasilkan minyak rata-rata 4 ton/ha (Ngalle et al, 2014), 6-10 kali lipat lebih banyak dibandingkan dengan minyak yang dihasilkan oleh kedelai, biji matahari, biji rapa, dan tanaman penghasil minyak nabati lainnya.…”
Section: Pendahuluanunclassified
“…merupakan tanaman C3 penghasil minyak nabati yang paling efisien (Lamade et al, 2009; Jaafar dan Ibrahim, 2012) dan mampu tumbuh pada berbagai agroekosistem (Firmansyah, 2014). Kelapa sawit mampu menghasilkan minyak rata-rata 4 ton/ha (Ngalle et al, 2014), 6-10 kali lipat lebih banyak dibandingkan dengan minyak yang dihasilkan oleh kedelai, biji matahari, biji rapa, dan tanaman penghasil minyak nabati lainnya.…”
Section: Pendahuluanunclassified
“…The growth of oil palm plantations in Indonesia has been inevitably rapid due to huge market of such commodities. Indonesia, together with Malaysia are known to have shares of 91% of crude palm oil production worldwide [6]. However, some negative images are still being connected to the presence of the oil palm plantations to the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…Massive land-use change, deforestation, crop and biodiversity loss have known to be attached to the oil palm plantation image [7]. On the other hand, several studies found that oil palm plantations are liked and lived in by many wild life diversities (mammals, birds, butterflies, and herpetofauna) [6], [8]. Added to these, some plantations own areas that are called high conservation value (HCV) areas.…”
Section: Introductionmentioning
confidence: 99%
“…According to the research of (Annisa and Rachman, 2016) with the shrink of agricultural land, the development of agricultural businesses on swamps is very important. According to (Aksani et al, 2016) the swamp natural ecosystem is fragile so it requires proper and integrated management to realize a sustainable farming system.…”
Section: Introductionmentioning
confidence: 99%